KOMPETENSI PROFESSIONAL GURU QUR’AN HADITS DI MTsN 8 PIDIE - Juairiah Umar (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Professional competence is the ability associated with the completion of teacher assignments. The professional competence of the Hadith Qur'an teachers is to develop plans for both objectives, a content of learning materials, methods, and techniques, as well as assessment, are the main elements that must be minimally present in every implementation of learning. How high is the relationship between the professional competence of the Qur'an Hadith teachers and the planning and implementation of learning in Pidie MTsN? This qualitative research collects data through observation, interviews, questionnaires, documentation and analyzed through descriptive analytics. The questionnaire was analyzed using Rating Scala, the number of respondents was 10, the items were also 10. The results showed the professional competence of the Qur'an 85% hadith approached